UJI KONSENTRASI EKSTRAK TEPUNG KULIT BUAH MANGGIS UNTUK MENGENDALIKAN PENYAKIT ANTRAKNOSA PADA BUAH CABAI - Rihat Silalahi; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to observe and obtain the best concentration of powder extract of mangosteen rind to control anthracnose disease on red chili fruits. The research has been conducted in the Laboratory of Plant Pathology, Agriculture Faculty, University of Riau from March to May 2017. The research has been conducted experimentally using a completely randomized design, consisted of 5 treatments and 4 replications. The research consisted of two tests: in vitro inhibition of C. capsici and in vivo application of powder extract of mangosteen rind on red chili fruits. The concentration of powder extract of extract mangosteen rind used were: 0%, 5%, 15%, 25% and 35%. The data were statistically analyzed using analysis of variance and the means were compared with Duncan 's New Multiple Range Test (DNMRT) at level of 5%. The results of the research showed that the concentration of powder extract of mangosteen rind significantly affected C. capsici growth and increase the percentage of fungal growth inhibition. Powder extract of mangosteen rind at concentration 35% gave the best effect in controlling anthracnose disease on red chilli fruits, which resulted in a longer incubation period of the disease, a lower intensity of the disease namely 23,70% and the effectiveness as a botanical fungicide is 60,47%. Key words : Red chili, the concentration and Garcinia mangostana.